-3(5w+v)-2(-3v+3w)=

Simple and best practice solution for -3(5w+v)-2(-3v+3w)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(5w+v)-2(-3v+3w)= equation:


Simplifying
-3(5w + v) + -2(-3v + 3w) = 0

Reorder the terms:
-3(v + 5w) + -2(-3v + 3w) = 0
(v * -3 + 5w * -3) + -2(-3v + 3w) = 0
(-3v + -15w) + -2(-3v + 3w) = 0
-3v + -15w + (-3v * -2 + 3w * -2) = 0
-3v + -15w + (6v + -6w) = 0

Reorder the terms:
-3v + 6v + -15w + -6w = 0

Combine like terms: -3v + 6v = 3v
3v + -15w + -6w = 0

Combine like terms: -15w + -6w = -21w
3v + -21w = 0

Solving
3v + -21w = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '21w' to each side of the equation.
3v + -21w + 21w = 0 + 21w

Combine like terms: -21w + 21w = 0
3v + 0 = 0 + 21w
3v = 0 + 21w
Remove the zero:
3v = 21w

Divide each side by '3'.
v = 7w

Simplifying
v = 7w

See similar equations:

| -5.6*-14.3= | | 342=23*b | | xy-xz=b-c | | -5.6x-14.3= | | -9x+13=-27 | | x-8=4-2(3x+5) | | 3d+8=6d-2 | | n+1=-17-10n-2+9n | | xy-zy=b-c | | -n-24=5-q | | 8x+38=3(x+1) | | xy-zy=b | | 2t^3-10t=t^2 | | 15-3x=15-3x | | 7x-6-4x=2x+6 | | 10-15x=35 | | 46-7x=12+10x | | 0.3333333333333333= | | 3xy+yx= | | 3x-4=6x-1 | | ax+bc+3=-6 | | -129=6(1-4n)-3n | | -(5w+u)+3(3u+5w)= | | 4z-5=19 | | 4x=4x+7 | | -4+5k=11 | | 3x^3+5x-8=0 | | (6-5s)(2-s)= | | 7+10r=77 | | 24+13=24+15 | | -30=2(w+5)-6w | | 2x+y-z=10 |

Equations solver categories